MALT lymphoma associated genetic aberrations occur at different frequencies in primary and secondary intestinal MALT lymphomas. Issue 11 (23rd March 2006) - Streubel, B; Seitz, G; Stolte, M; Birner, P; Chott, A; Raderer, M
Abstract : Background and aims: Limited data are available on intestinal MALT lymphoma owing to its relatively rare occurrence. The frequency of associated genetic changes was therefore analysed in intestinal MALT lymphoma to determine whether primary and secondary examples may be distinguished by their genetic profile. Methods: Patients diagnosed with MALT lymphoma involving the intestine were evaluated and compared with 71 cases with localised gastric MALT lymphoma. Paraffin embedded samples were evaluated for t(11;18)(q21;q21) by reverse transcription polymerase chain reaction, and by fluorescence in situ hybridisation for t(14;18)(q32;q21), t(1;14)(p22;q32), and trisomies 3 and 18. Results: 30 consecutive patients with MALT lymphoma involving the intestine were identified: 16 had primary intestinal lymphoma and 14 had secondary MALT lymphoma. t(11;18)(q21;q21) was found in one third of the patients, but there was a significant difference between the secondary MALT lymphomas and the primary intestinal and gastric MALT lymphoma groups (57% v 12.5%, p = 0.019, and 57% v 24%, p = 0.022). Two patients with primary intestinal MALT lymphomas were positive for t(1;14)(p22;q32) and none was positive for t(14;18)(q32;q21). Primary intestinal MALT lymphoma had a significantly higher frequency of trisomies 3 or 18 (81% v 36%, p = 0.024; 81% v 14%, p<0.001), in contrast to secondary intestinal MALT lymphomas and localised gastric MALT lymphomas. Conclusions: The genetic profile of primary intestinal MALT lymphomas appears to be different from that of secondary intestinal or local gastric MALT lymphomas. Because of the high prevalence of trisomy 3 or 18, or both, in primary intestinal lymphoma, these numerical aberrations might be regarded as a genetic hallmark of the disease.